2016
DOI: 10.1063/1.4967253
|View full text |Cite
|
Sign up to set email alerts
|

Dual hydrogen-bonding motifs in complexes formed between tropolone and formic acid

Abstract: The near-ultraviolet π←π absorption system of weakly bound complexes formed between tropolone (TrOH) and formic acid (FA) under cryogenic free-jet expansion conditions has been interrogated by exploiting a variety of fluorescence-based laser-spectroscopic probes, with synergistic quantum-chemical calculations built upon diverse model chemistries being enlisted to unravel the structural and dynamical properties of the pertinent ground [X̃A] and excited [ÃAππ] electronic states. For binary TrOH ⋅ FA adducts, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 107 publications
1
4
0
Order By: Relevance
“…Their DF counterparts show spectral shifts and bifurcations that depend on the nature of the underlying vibrational motion, with the Δ υ X̃ metrics measured for several ground-state features highlighted [ν 0 ( a 1 ) denotes the zero-point level]. These results build on laser-spectroscopic techniques and HFF-synthesis procedures , reported elsewhere (cf. Supporting Information for details).…”
supporting
confidence: 61%
“…Their DF counterparts show spectral shifts and bifurcations that depend on the nature of the underlying vibrational motion, with the Δ υ X̃ metrics measured for several ground-state features highlighted [ν 0 ( a 1 ) denotes the zero-point level]. These results build on laser-spectroscopic techniques and HFF-synthesis procedures , reported elsewhere (cf. Supporting Information for details).…”
supporting
confidence: 61%
“…Acquisition of rotationally resolved LIF data for the HFF Ã – X̃ origin band exploited a similar configuration based on a higher resolution dye-laser source (Lambda Physik FL3002E; Exciton 428 dye dissolved in p -dioxane; tunable intracavity etalon yielding a time-averaged bandwidth of ≤0.03 cm –1 fwhm) that was pumped by the third harmonic of a separate injection-seeded Nd:YAG system (Spectra-Physics PRO-250-20; 20 pps repetition rate, ∼10 ns pulse duration). Both tunable dye-laser platforms were combined to conduct a limited series of fluorescence hole-burning (FHB) studies designed to assess the common parentage of observed spectral signals …”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…Both tunable dye-laser platforms were combined to conduct a limited series of fluorescence hole-burning (FHB) studies designed to assess the common parentage of observed spectral signals. 66 Experiments were performed in a stainless-steel vacuum vessel evacuated to a base pressure of <10 −7 Torr by means of a liquidnitrogen baffled oil diffusion pump (Varian VHS-6 with 362−6 cold trap) backed by a mechanical rotary pump (Leybold D65B). Target molecules were cooled rovibrationally through entrainment of their ambient (25 °C) vapor in a supersonic freejet expansion of ultrapure helium carrier gas as formed by a pulsed valve of the current-loop actuated design (R. M. Jordan C-211SS; modified for 20pps operation).…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 For nearly as long, tropolone ( 5 ) has been known to be weakly fluorescent, and its absorbance and fluorescence intensity varies based on pH and solvent. 9 In more recent years, however, tropolone fluorescence has been found to be responsive to various environmental changes, including gases, 10 metals, 11 and other exogenous additives 12 that could make it a valuable tool for fluorescence small molecule development. However, tropolone's fluorescence is weak, with a reported quantum yield in cyclohexane of only 0.5% and even weaker in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%